A Novice Teacher's Perceptions Of Her Different Roles As An English Language Teacher - Astuti, Irma Windy (English Education Department, Universitas Islam Indonesia, 2010)
This paper is a study investigating the different roles of English language teacher as they are particularly perceived by a novice English teacher. I am primarily interested in knowing and understanding how a novice teacher perceives her different roles as an English language teacher given her status as a beginning teacher who may still be relatively new in her teaching profession. Hence, being perceived as a new, and therefore, a less experienced one, her accounts and take on her different teaching roles are valuable to learn as they may reflect her pedagogical knowledge, limitations, expectations and the challenges she may face in assuming her different roles as an English language teacher which may as well be quite different from those of more senior or experience English language teachers.This study is a progressive qualitative. The data, in a form of texts, were presented and analyzed based on the narratives of the research participant. The use of narrative research inquiry was intended to seek insightful meanings and understandings of the individual's perceptions of her different roles as an English language teacher. The data were taken both from interviews and classroom observations.The findings of this study underline the participant's sound grasp and firm understanding of her various teaching roles and reveal a range of roles she had to perform involving thoughtful considerations of her teaching practices. Based on the findings of this study, it is recommended that a further or subsequent research conducted within a similar topic may also try to solely focus on one of the findings of the perceived teacher's roles in order to gain a deeper insight on it. A probable research may therefore investigate the degree of each role to see how it comes into being, what related factors may come into play and what constraints as well as challenges may come with each and or with all of the teaching role(s).Alternatively, a related study may also attempt for a comparative study investigating the similarities and differences of the various teaching roles perceived by both novice teachers and more experienced teachers. Finally, there may also be a need for an investigation on the students' perceptions towards English language teachers' various and effective roles in relation to their learning.